2021
DOI: 10.1021/acsnano.0c07982
|View full text |Cite
|
Sign up to set email alerts
|

Impact of S-Vacancies on the Charge Injection Barrier at the Electrical Contact with the MoS2 Monolayer

Abstract: Making electrical contacts to semiconducting transition metal dichalcogenides (TMDCs) represents a major bottleneck for high device performance, often manifesting as strong Fermi level pinning and high contact resistance. Despite intense ongoing research, the mechanism by which lattice defects in TMDCs impact the transport properties across the contact–TMDC interface remains unsettled. Here we study the impact of S-vacancies on the electronic properties at a MoS2 monolayer interfaced with graphite by photoemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
8
28
0
Order By: Relevance
“…More recently, Bussolotti et al have indicated that the Fermi level can also be pinned at the deep sulfur-vacancy gap state in defective MoS 2 controlled by argon sputtering, measured by using X-ray photoelectron spectroscopy (XPS) and angle-resolved photoemission spectroscopy. [40] Figure 4d shows that the location of the FLP is tuned toward the valence band edge with an increased concertation of deep sulfur vacancies, therefore limiting electron injection to MoS 2 with a considerable barrier. Such limitations are mostly absent for hole injection as the shallow sulfur-vacancy gap states pin Fermi level close to the valence band minimum (VBM).…”
Section: Extrinsic Contributorsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Bussolotti et al have indicated that the Fermi level can also be pinned at the deep sulfur-vacancy gap state in defective MoS 2 controlled by argon sputtering, measured by using X-ray photoelectron spectroscopy (XPS) and angle-resolved photoemission spectroscopy. [40] Figure 4d shows that the location of the FLP is tuned toward the valence band edge with an increased concertation of deep sulfur vacancies, therefore limiting electron injection to MoS 2 with a considerable barrier. Such limitations are mostly absent for hole injection as the shallow sulfur-vacancy gap states pin Fermi level close to the valence band minimum (VBM).…”
Section: Extrinsic Contributorsmentioning
confidence: 99%
“…Reproduced with permission. [ 40 ] Copyright 2021, American Chemical Society. SV and DV in (c) stand for single line vacancy and double line vacancy, respectively.…”
Section: Fundamentals Of Fermi Level Pinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Using DFT, we made an ab initio analysis of the electronic states of graphene–MoS 2 in the presence of sulfur vacancies: These have an energy that falls in the gap of MoS 2 and are located at a distance of few Angstroms from graphene, so their effect is hard to evaluate without a first-principles approach (see the “Methods” section and the Supporting Information for further details). Numerical calculations were performed using a density of S-vacancies of ρ v ≈ 1.8 × 10 13 cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the enhanced catalytic efficacies of the Co/MoS 2 @N,S-CHNSs, DFT calculations are performed to investigate the HER process at the atomic level. [54][55][56] The computational model of Co/MoS 2 heterojunction is built by coupling the Co(111) facet with the MoS 2 (002) facet (Figure 6A). The optimized geometry structure of Co/MoS 2 indicates that metallic Co strongly connects with MoS 2 through the S-edge atoms at the interface.…”
Section: Introductionmentioning
confidence: 99%